Stem cell biology and regenerative medicine - Durand, Charles (River Publishers series in biotechnology and medical technology forum., 2021)
The study of stem cell biology is under intensive investigation. Because stem cells have the unique capability to self-renew and differentiate into one or several cell types, they play a critical role in development, tissue homeostasis and regeneration. Stem cells also constitute promising cell candidates for cell and gene therapy. The aim of this book is to provide readers and researchers with timely and accurate knowledge on stem cell biology and regenerative medicine. This book will cover many topics in the field and is based on conferences given by recognized scientists involved in the international master course on stem cell biology at Sorbonne Université in Paris.